A systematic review on radiofrequency assisted laparoscopic liver resection: Challenges and window to excel. (September 2017) - Reccia, Isabella; Kumar, Jayant; Kusano, Tomokazu; Zanellato, Artur; Draz, Ahmed; Spalding, Duncan; Habib, Nagy; Pai, Madhava
Abstract: Laparoscopic liver resection has progressively gained acceptance as a safe and effective procedure in the treatment of benign and malignant liver neoplasms. However, blood loss remains the major challenge in liver surgery. Several techniques and devices have been introduced in liver surgery in order to minimize intraoperative haemorrhage during parenchymal transection. Radiofrequency (RF)-assisted liver resection has been shown to be an effective method to minimize bleeding in open and laparoscopic liver resection. A number of RF devices for parenchymal transection have been designed to assist laparoscopic liver resections. Here we have reviewed the results of various RF devices in laparoscopic liver resection. A total 15 article were considered relevant for the evaluation of technical aspects and outcomes of RF-assisted liver resections in laparoscopic procedures. In these studies, 176 patients had laparoscopic liver resection using RF-assisted parenchymal coagulation. Two monopolar and three bipolar devices were employed. Blood loss was limited in most of the studies. The need of blood transfusions was limited to two cases in all the series. Conversion was necessary due to bleeding in 3 cases. Operative and transection times varied between studies. However, RF-assisted resection with bipolar devices appeared to have taken less time in comparison to other RF devices. RF-related complications were minimum, and only one case of in-hospital death due to hepatic failure was reported. Although RF has been used in a small minority of laparoscopic liver resections, laparoscopic RF-assisted liver resection for benign and malignant disease is a safe and feasible procedure associated with reduction in blood loss, low morbidity, and lower hospital mortality rates. Highlights: Laparoscopic liver resection is a safe and effective procedure, although blood loss is still a challenge. Among different devices, Radiofrequency (RF) can help in minimizing blood loss in open and laparoscopic liver resection. RF has been used in small minority of cases, it seems to be safe with less blood loss, low morbidity and lower mortality. With RF, resection and ablation can be combined during same procedure. Current results support the use of RF as precoagulation device in laparoscopic liver surgery.